2010
DOI: 10.1177/0886260509354515
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Revictimization During Women’s First Year of College: Self-Blame and Sexual Refusal Assertiveness as Possible Mechanisms

Abstract: Although sexual victimization during adolescence increases risk for later revictimization, mechanisms for increased risk among new college students have not been identified. Female undergraduates (N = 87) were assessed at the start and end of their first academic year. Those who reported initial sexual victimization at Time 1 were more likely than other women to report later college victimization at Time 2. Path analyses showed that self-blame and decreased sexual refusal assertiveness (SRA) explained this eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
69
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 30 publications
(43 reference statements)
6
69
2
1
Order By: Relevance
“…This extends previous findings showing that victimization history is associated not only with trauma-related guilt and shame but also with generalized guilt and shame (Dorahy and Clearwater, 2012;Katz et al, 2010;Miller et al, 2010).…”
Section: Traumatized Versus Nontraumatized Womensupporting
confidence: 84%
See 1 more Smart Citation
“…This extends previous findings showing that victimization history is associated not only with trauma-related guilt and shame but also with generalized guilt and shame (Dorahy and Clearwater, 2012;Katz et al, 2010;Miller et al, 2010).…”
Section: Traumatized Versus Nontraumatized Womensupporting
confidence: 84%
“…To date, most studies on guilt, shame, and trauma as well as most therapeutic approaches refer to guilt and shame specifically related to the traumatic event (Andrews et al, 2000;Ginzburg et al, 2009;Katz et al, 2010;Kletter et al, 2009;Øktedalen et al, 2015). Posttraumatic guilt, for example, often refers to "survivor guilt" or "self-recrimination for failed actions that the individual believes would have created a more salutary outcome" of the traumatic event (Wilson et al, 2006, p. 130).…”
mentioning
confidence: 97%
“…Indeed, women with a history of SV reported decreased sexual assertiveness (Stoner et al, 2008), were subsequently more willing to consent to unwanted sex even though their partner did not use coercive tactics during that sexual encounter (Katz & Tirone, 2010), and were more willing to abdicate to a partner’s desire for unprotected sex (George et al, 2016). Moreover, college women who blame themselves for an earlier SV exhibit a significant decrease in their sexual refusal assertiveness (Katz, May, Sörensen, & DelTosta, 2010). …”
Section: Sv History As a Risk Factor For Coerced Consensual Sexmentioning
confidence: 99%
“…Low assertiveness has been associated with sexual victimization and revictimization [27][29]. Gidycz et al [30] found that women's low assertiveness was predicted by experiences of child sexual abuse.…”
Section: Introductionmentioning
confidence: 99%